2020
DOI: 10.2340/16501977-2694
|View full text |Cite
|
Sign up to set email alerts
|

Long-term clinical outcomes in survivors of severe acute respiratory syndrome and Middle East respiratory syndrome coronavirus outbreaks after hospitalisation or ICU admission: A systematic review and meta-analysis

Abstract: Severe acute respiratory syndrome (SARS) and Middle East Respiratory Syndrome (MERS) are two previous viral infection outbreaks similar to the current COVID-19 pandemic. Studies that have looked at long-term health problems in survivors of these two outbreaks report reduced lung function and reduced ability to exercise in some survivors up to 6 months after discharge from hospital. Mental health problems including stress, anxiety and depression were observed in up to one-third of survivors at 6 months and beyo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

55
447
6
34

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 498 publications
(542 citation statements)
references
References 19 publications
55
447
6
34
Order By: Relevance
“…Considering the widespread prevalence of COVID-19, the long-term complications of coronavirus infection in survivors will increase healthcare utilization significantly in the coming months. Previous outbreaks have shown that there is a broad spectrum of long-term complications of coronavirus infection which spans across all of the ICF components, with prevalence of respiratory compromise, exercise intolerance, psychological distress and reduced quality of life being considerably high several months following infection [5]. Deficits in different components do not necessarily translate into each other and there is no causal relationship between them [15].…”
Section: Discussionmentioning
confidence: 99%
“…Considering the widespread prevalence of COVID-19, the long-term complications of coronavirus infection in survivors will increase healthcare utilization significantly in the coming months. Previous outbreaks have shown that there is a broad spectrum of long-term complications of coronavirus infection which spans across all of the ICF components, with prevalence of respiratory compromise, exercise intolerance, psychological distress and reduced quality of life being considerably high several months following infection [5]. Deficits in different components do not necessarily translate into each other and there is no causal relationship between them [15].…”
Section: Discussionmentioning
confidence: 99%
“…All of Ireland's population are susceptible to COVID-19 infection 5,6 . Patients present with fever, cough, dyspnoea, fatigue, with some developing acute respiratory distress syndrome, multi-organ damage and secondary infection 7,8 . Symptoms of COVID-19 infection vary between individuals, and according to disease severity 5,7,9 .…”
Section: Introductionmentioning
confidence: 99%
“…Patients present with fever, cough, dyspnoea, fatigue, with some developing acute respiratory distress syndrome, multi-organ damage and secondary infection 7,8 . Symptoms of COVID-19 infection vary between individuals, and according to disease severity 5,7,9 . Many are asymptomatic 10 , some show mild to moderate symptoms 5,7 although severe cases with acute respiratory distress syndrome, acute heart injury, and secondary bacterial infection have occurred 5,9 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increasing SRs during the SARS, MERS, and COVID-19 pandemics were focusing on depression. [ 11 , 17 24 ] However, the methodological quality of these SRs is unclear. Therefore, to evaluate and compare the normativity of report of SR, we conducted a comprehensive overview about prevalence of depression during the SARS, MERS, and COVID-19 pandemics.…”
Section: Introductionmentioning
confidence: 99%